2017
DOI: 10.1080/00207454.2017.1366475
|View full text |Cite
|
Sign up to set email alerts
|

Facial emotion decoding in patients with Parkinson's disease

Abstract: The present study provides further evidence of altered non-verbal emotional information processing in Parkinson's disease patients, suggesting that nigrostriatal dopaminergic depletion leads also to emotional information processing dysfunction. The consequences of these emotional encoding disturbances in daily living and their relationship to mood and behavioural disorders remain to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
1
9
1
Order By: Relevance
“…predominant right side PD motor symptom onset PwPD was small in magnitude, and did not attain significance. As noted earlier, the typical unilateral motor symptom onset of PD is associated with more pronounced dopaminergic denervation contralateral to the presenting symptoms (De Risi et al, 2018;Stirnimann et al, 2018). Consequently, these data align with other literature showing a potential right hemispheric specialisation of emotional and social processing (e.g.…”
Section: A C C E P T E Dsupporting
confidence: 90%
See 1 more Smart Citation
“…predominant right side PD motor symptom onset PwPD was small in magnitude, and did not attain significance. As noted earlier, the typical unilateral motor symptom onset of PD is associated with more pronounced dopaminergic denervation contralateral to the presenting symptoms (De Risi et al, 2018;Stirnimann et al, 2018). Consequently, these data align with other literature showing a potential right hemispheric specialisation of emotional and social processing (e.g.…”
Section: A C C E P T E Dsupporting
confidence: 90%
“…This was an important question to address, because for PwPD, the onset of motor symptoms is typically unilateral. This asymmetry is associated with more pronounced dopaminergic denervation in the basal ganglia, contralateral to the presenting symptoms (De Risi et al, 2018;Stirnimann et al, 2018), with this pattern said to persist even after motor symptom presentation becomes bilateral (Garrido-Vásquez et al, 2012;Ille et al, 2016). As there is some evidence for right hemispheric specialisation for emotional and social processing (e.g.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Impairments of facial emotion recognition in PD patients were found to be independent of depressive symptoms [ 167 , 179 - 181 ], executive deficits [ 179 , 180 ], and clinical aspects (i.e., disease duration and severity, [ 180 ]). Moreover, some studies revealed that emotion recognition abnormalities may occur after subthalamic nucleus stimulation [ 182 - 185 ], probably due to alterations of projections to cortical areas, particularly the OFC, which has been already implicated in emotion recognition [ 186 ].…”
Section: Social Cognition Abnormalities In Neurodegenerative Disormentioning
confidence: 99%
“…Several studies revealed deficits in emotion recognition in PD patients with respect to healthy controls. [36][37][38] However, other studies failed to confirm these deficits. [39,40] A meta-analytic review, [41] investigated facial and vocal emotion recognition of PD patients, revealed significant and modest alterations of this ability independently from the level of motor symptoms.…”
Section: Social Cognition Abnormalities In Parkinson's Disease and In Parkinsonismmentioning
confidence: 99%